Resolving an apparent discrepancy between theory and experiment: spin–spin coupling constants for FCCF - Del Bene, Janet E. (2008)
Ab initio equation of motion coupled cluster singles and doubles (EOM–CCSD) and second-order polarization propagator approximation (SOPPA) calculations have been performed to evaluate spin–spin coupling constants for FCCF (difluoroethyne). The computed EOM-CCSD value of 3J(F–F) obtained at the experimental geometry of this molecule supports the previously reported experimental value of 2.1 Hz, thereby resolving an apparent discrepancy between theory and experiment. This coupling constant exhibits a strong dependence on the C–C and C–F distances, and its small positive value results from a sensitive balance of paramagnetic spin-orbit (PSO) and spin-dipole (SD) terms. The three other unique FCCF coupling constants 1J(C–C), 1J(C–F), and 2J(C–F) have also been reported and compared with experimental data. While 1J(C–F) is in agreement with experiment, the computed value of 2J(C–F) is larger than our estimate of the experimental coupling constant.